Development of Sensory Path Games to Improve Gross Motor Skills in Early Childhood - Syahrani, St. Aisyah; Suardi, Suardi; Rusmayadi, Rusmayadi; Herlina, Herlina; Kurnia, Rika; Musi, Muhammad Akil (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
This study aims to develop sensory path games to improve gross motor skills in early childhood. The specific objectives of this research include (1) determining the level of need for sensory path game development; (2) designing a prototype of the game; (3) determining the level of validity and practicality of the developed media; and (4) measuring the effectiveness of its use. This research employs the ADDIE development model, which comprises the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 15 children and class teachers at Permata Bahari Islamic Kindergarten. Data collection techniques used observation, interviews, documentation, and questionnaires. The results showed that the media were classified as very valid (81.7%), very practical (89.75%), and very effective (90.55%) in improving children's gross motor skills. Thus, sensory path games are feasible to use as innovative learning media in the Early Childhood Education environment.